Literature review, report, and analysis of genotype and clinical phenotype of a rare case of ulnar-mammary syndrome - Zhang, Xiwen; Chen, Lifen; Li, Lin; An, Jingjing; He, Qinyu; Zhang, Xuelei; Lu, Wenli; Xiao, Yuan; Dong, Zhiya (Frontiers in Pediatrics, 2023)
Objective: The clinical characteristics of Ulnar-mammary syndrome (UMS) caused by mutations in TBX3 (T-Box transcription factor 3) were studied and the correlation between genotype and clinical phenotype were analyzed to improve awareness and early diagnosis of the disease. Methods: The clinical data of a boy aged 13 years and 5 months with left forearm deformity and growth retardation as the main features were analyzed. Genomic exon detection was performed, and the results were verified by Sanger sequencing. Simultaneously, we performed literature review to analyze the correlation between clinical phenotypes and genotypes. Results: The clinical manifestations in the child were short stature, ulnar hypoplasia of the forearm, hypohidrosis, retracted nipple, micropenis, and cryptorchidism. Laboratory examination revealed hyperthyroidism, growth hormone deficiency, and hypogonadotropic hypogonadism. Imaging results displayed delayed bone age, small pituitary gland, and persistence of Rathke’s cleft cyst. The results of the exome sequencing revealed the deletion of AGA at positions 1121–1124 of TBX3, which resulted in a frameshift mutation (c.1121–1124del AGAG; pGlu374fs). According to the American College of Medical Genetics (ACMG) assessment, the mutation is a pathogenic variant. A definitive diagnosis of UMS was made on the basis of the clinical phenotype of the patient. The Chinese and English literature were reviewed to analyze the correlation between TBX3 genotype and clinical phenotype. Conclusion: UMS is a rare hereditary disease caused by mutations in TBX3. There is significant clinical heterogeneity associated with the variants of this gene. To our knowledge, this mutation site in TBX3 has been reported for the first time, thereby expanding the mutation spectrum of this gene.